Electrochemical Deposition of Lead for Water Quality Sensing. Issue 1 (18th January 2022) - Nelson, Anna M.; Habibi, Sanaz; Lee, Jaesung; Burns, Mark A.
Abstract : Lead contamination in drinking water can pose serious health risks to humans, and can often go undetected as a result of corrosion of lead infrastructure installed in buildings constructed prior to 1986. Thus, there is an unmet need for timely, cost-effective, and onsite monitoring of lead in drinking water. Here, we have designed a four-electrode system to reliably respond to electrodeposited lead oxide that provides a near real-time indication of lead presence. To better understand this detection mechanism, we investigated the temporal and spatial electrochemical deposition of lead using potential response data, scanning electron microscopy (SEM), fractal dimension ( f D ), and COMSOL Multiphysics® finite element analysis. Our results suggest that the deposition of lead oxide on the sensor is diffusion limited. Such fundamental understanding of the detection mechanism is critical to improve and shorten the detection time of the sensor. We used this information to improve the detection time and reliability of the signal by reducing the electrode gap distance and agitating the solution. This study provides a path for further optimization of a continuous electrochemical sensor for onsite monitoring of lead in drinking water.